2020
DOI: 10.1016/j.ekir.2019.11.020
|View full text |Cite
|
Sign up to set email alerts
|

The Marginal Cost of Frailty Among Medicare Patients on Hemodialysis

Abstract: Introduction: Dialysis patients incur disproportionately high costs compared with other Medicare beneficiaries. Care for frail individuals may be even more costly. We examined the extent to which frailty contributes to higher costs among dialysis patients. Methods: We used ACTIVE/ADIPOSE (A Cohort to Investigate the Value of Exercise/Analyses Designed to Investigate the Paradox of Obesity and Survival in ESRD) enrollees (adult hemodialysis patients evaluated from June 2009 to August 2011) in a retrospective co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Our study focused on MPI and outcomes also in patients on replacement therapy, considering the clinical relevance of predicting hospitalizations and survival in HD and PD patients. In this light, recent data showed that HD patients with frailty incurred higher healthcare costs with respect to those without frailty over a mean follow-up of 2.3 years [8]. In addition, we have previously shown that HD patients may present neurological and psychological dysfunctions that were associated with impaired quality of life [19].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our study focused on MPI and outcomes also in patients on replacement therapy, considering the clinical relevance of predicting hospitalizations and survival in HD and PD patients. In this light, recent data showed that HD patients with frailty incurred higher healthcare costs with respect to those without frailty over a mean follow-up of 2.3 years [8]. In addition, we have previously shown that HD patients may present neurological and psychological dysfunctions that were associated with impaired quality of life [19].…”
Section: Discussionmentioning
confidence: 92%
“…Studies support the idea that multidimensional assessment represents an important aspect in predicting shortand long-term all-cause mortality in older CKD patients [5][6][7]. This is crucial also in considering the high prevalence of frailty in this population negatively impacting on several outcomes [8].…”
Section: Introductionmentioning
confidence: 94%
“…13 Fried frailty phenotype was defined as the presence of 3 or more of the following five criteria: weight loss, exhaustion, low physical activity, slow gait speed, and weakness. 4,11 Weight loss was defined as having more than 10 pounds unintentional weight loss over the preceding 12 months. 5 Exhaustion was defined as having a positive response to two questions regarding endurance and energy from the Center for Epidemiological Studies Depression questionnaire.…”
Section: Comorbidities and Frailtymentioning
confidence: 99%
“…5,[8][9][10] In a broader perspective, the cost of medical treatment for ESKD patients is already inordinate compared to other diseases and frailty only perpetuates this disproportionality within the dialysis population. 11 The underutilization of frailty as a modifiable disease state to improve mortality in dialysis patients stems mainly from the lack of a universal operational definition. Operational definitions of frailty are divided into three constructs: physical construct of frailty or frail phenotype, subjective construct of frailty or the frailty score, and a deficit construct of frailty better known as the frailty index.…”
Section: Introductionmentioning
confidence: 99%
“…The patients were followed for 3 years with frailty and laboratory measurements assessed at baseline, 12, and 24 months. The procedure for obtaining demographic and comorbid conditions and a description of lab processing have been described in a previous study [17,18].…”
Section: Patients Demographic and Laboratory Measuresmentioning
confidence: 99%